2011
DOI: 10.1111/j.1600-0706.2011.19558.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought changes plant chemistry and causes contrasting responses in lepidopteran herbivores

Abstract: Deutscher Wetterdienst DWD, German Federal Ministry of Transport, Building and Urban Affairs. † MeteoSwiss, Swiss Federal Offi ce of Meteorology and Climatology. * Statistical analyses were conducted for each plant series with 'drought stress' and 'plant population' as fi xed factors in two-way ANOVAs (signifi cant effects in bold) followed by LSD post hoc tests (shown in brackets).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
201
7
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(224 citation statements)
references
References 63 publications
10
201
7
6
Order By: Relevance
“…Therefore, it can be inferred that the dry zone environment has not significantly affected the production and composition of secondary metabolites in the leaves of P. betle, during this study. The work of Gutbrodt et al (2011) also shows that water stress leads to low concentrations of secondary defense compounds in plants which are severely stressed. However, according to Taiz and Zeiger (1991), the production of secondary metabolites is increased when the plant is under stress including water stress and pathogen attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be inferred that the dry zone environment has not significantly affected the production and composition of secondary metabolites in the leaves of P. betle, during this study. The work of Gutbrodt et al (2011) also shows that water stress leads to low concentrations of secondary defense compounds in plants which are severely stressed. However, according to Taiz and Zeiger (1991), the production of secondary metabolites is increased when the plant is under stress including water stress and pathogen attack.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more secondary metabolites are produced when the plant is under stress including water stress and pathogen attack (Taiz and Zeiger, 1991). Controversially, it is also reported that water stress leads to low concentrations of secondary metabolites in plants (Gutbrodt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, plant drought stress will also have consequences for herbivores and their interactions with plants (Cornelissen, 2011). Drought and high temperature conditions are often associated with herbivore outbreaks (Mattson and Haack 1987), but both positive and negative effects on herbivores have been reported depending on the severity of the stress and differing across species and across the plants they are attacking (Huberty and Denno, 2004;Cornelissen et al, 2008;White 2009;Gutbrodt et al, 2011). Yet, plant responses to a combination of abiotic (e. g. drought stress) and biotic (e. g. herbivory)…”
Section: Introductionmentioning
confidence: 99%
“…The resulting performance of phytophagous arthropods on drought-stressed plants will then depends on the access they have to an optimal balance of nutrients in the plant according to their feeding habit (Huberty and Denno, 2004), and their adaptation to plant defense compounds according to their grade of specialization (Gutbrodt, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation